Making music on the march: sledging songs of the 'heroic age' of Antarctic exploration - Carolyn Philpott; Elizabeth Leane (2016)
During the so-called 'heroic age' of Antarctic exploration (c.1897‚Äö-1922), various parties of men invented songs to aid the act of sledging and to provide a mental diversion from the monotony of the task and the physical demands it made on the human body. Songs composed in this uniquely polar musical genre typically included rhyming lyrics that were highly motivational and expressed a united identity. The lyrics were usually set to the melodies of popular songs of the day. When voiced in unison by men out 'on the march,' sledging songs could help to promote team synchronisation and cohesion, and give the act of sledging (as well as the expeditions as a whole) a stronger sense of purpose and meaning. The singing of such songs, therefore, contributed in a very practical way to the overall success of many Antarctic expeditions of the 'heroic age'. This article examines three sledging songs dating from this period of Antarctic exploration and investigates the historical context in which they were created and performed. It also considers what these songs reveal about the experiences of the men who participated in the sledging journeys and their earliest perceptions of the Antarctic environment.